New Brilliant Blue G Derivative as Pharmacological Tool in Retinal Surgery - Angelo Spadaro; Marco Rao; Miriam Lorenti; Mario Rosario Romano; Antonio Augello; Chiara Maria Eandi; Chiara Maria Eandi; Chiara Bianca Maria Platania; Filippo Drago; Filippo Drago; Claudio Bucolo; Claudio Bucolo (Frontiers Media S.A., 2020)
Our study was aimed at assessing the retinal binding of a new synthetic Brilliant Blue G (BBG) derivative (pure benzyl-Brilliant Blue G; PBB) ophthalmic formulation, to improve vitreoretinal surgery procedure. Protein affinity of the new molecule was evaluated in vitro (cell-free assay) and in silico. Furthermore, an ex vivo model of vitreoretinal surgery was developed by using porcine eyes to assess the pharmacological profile of PBB, compared to commercial formulations based on BBG and methyl-BBG (Me-BBG). PBB showed a higher affinity for proteins (p < 0.05), compared to BBG and Me-BBG. In vitro and in silico studies demonstrated that the high selectivity of PBB could be related to high lipophilicity and binding affinity to fibronectin, the main component of the retinal internal limiting membrane (ILM). The PBB staining capabilities were evaluated in porcine eyes in comparison with BBG and Me-BBG. Forty microliters of each formulation were slowly placed over the retinal surface and removed after 30 s. After that, ILM peeling was carried out, and the retina collected. BBG, Me-BBG, and PBB quantification in ILM and retina tissues was carried out by HPLC analysis. PBB levels in the ILM were significantly (p < 0.05) higher compared to BBG and Me-BBG formulations. On the contrary, PBB showed a much lower (p < 0.05) distribution in retina (52 ng/mg tissue) compared to BBG and Me-BBG, in particular PBB levels were significantly (p < 0.05) lower. Therefore, the new synthetic Brilliant Blue derivative (PBB) showed a great ILM selectivity in comparison to underneath retinal layers. In conclusion, these findings had high translational impact with a tangible improving in ex vivo model of retinal surgery, suggesting a future use during surgical practice.